2022
DOI: 10.3390/curroncol29060344
|View full text |Cite
|
Sign up to set email alerts
|

Female Healthcare Workers’ Knowledge, Attitude towards Breast Cancer, and Perceived Barriers towards Mammogram Screening: A Multicenter Study in North Saudi Arabia

Abstract: Breast cancer is the most commonly diagnosed cancer among women in the Kingdom of Saudi Arabia and other Middle East countries. This analytical cross-sectional study assessed knowledge, attitude towards breast cancer, and barriers to mammogram screening among 414 randomly selected female healthcare workers from multiple healthcare facilities in northern Saudi Arabia. Of the studied population, 48.6% had low knowledge, and 16.1% had a low attitude towards breast cancer risk factors and symptoms. The common barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
3
6
1
Order By: Relevance
“…Another important impediment to breast cancer screening in this study was the fear of detecting a tumor. Similar to our findings, Alenezi et al discovered that fear of detecting breast cancer was another important barrier to breast cancer screening in Saudi Arabian women [ 24 ]. This information may help target educational programs to improve breast cancer screening.…”
Section: Discussionsupporting
confidence: 91%
“…Another important impediment to breast cancer screening in this study was the fear of detecting a tumor. Similar to our findings, Alenezi et al discovered that fear of detecting breast cancer was another important barrier to breast cancer screening in Saudi Arabian women [ 24 ]. This information may help target educational programs to improve breast cancer screening.…”
Section: Discussionsupporting
confidence: 91%
“…Alenezi et al performed a cross-sectional study in Saudi Arabia among 414 randomly selected female healthcare workers to assess their level of knowledge, attitude to breast cancer and barriers to mammography screening [ 9 ]. A high rate of a lack of knowledge was found, with 48.6% of the health care workers having a very low knowledge of breast cancer, and there was a significant negative correlation between a lack of knowledge and barriers to screening.…”
Section: Knowledge About Screening and The Overdetection Of Breast Ca...mentioning
confidence: 99%
“…Zohre Momenimovahed et al reviewed 71 papers and found that barriers to mammography screening in Asia include factors such as personal beliefs, fatalism, fear of pain and embarrassment, religion, lack of support from loved ones, sociodemographic factors, and financial constraints [ 99 ]. Additionally, studies done in Japan, Kuwait, Iran, China, Saudi Arabia, Jordan, South Korea, Singapore, and Brunei found that a lack of awareness of breast cancer and mammography screening, religion, financial cost, personal fear, and low health literacy/education were listed as reasons hindering women from obtaining mammography screening [ 24 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Findings and Interpretationsmentioning
confidence: 99%